Improvement of the interfacial shear strength of poly(p‐phenylene benzobisoxazole) fiber/epoxy resin composite via a novel surface coating agent. Issue 4 (23rd December 2014) - Liu, Rongbiao; Han, Zhewen; Li, Weifeng; Li, Xinxin; Zhuang, Qixin
Abstract : Poly( p ‐phenylene benzobisoxazole) (PBO) fiber with a smooth surface exhibits limited interfacial interaction with resin matrix. One of the effective strategies to improve the adhesion between the fiber and resin matrix is through surface modification of the fiber. In this study, we have proposed a novel surface treatment agent based on phosphoester cross‐linked castor oil (PCCO) for effective surface treatment of PBO fibers. The surface treatment agent was prepared by a simple cross‐linking reaction between hydroxy phosphorylated castor oil (PCO) and epoxy resin, with alcohol as the solvent at 65°C. Once the PBO fiber was treated with this agent, the interfacial adhesion between the PBO fiber and the epoxy resin could then be improved. Systematic analyses suggest that the surface treatment with (PCO + epoxy)/alcohol solution improves the interaction of the PBO fiber with the epoxy resin matrix. The PCCO coated onto the surface of PBO fiber acts as a coupling agent, improving the interfacial shear strength (IFSS) of the PBO fiber/epoxy resin composite. Results indicate a 156% increase in IFSS without compromising the mechanical properties of the fiber. POLYM. COMPOS., 37:1198–1205, 2016. © 2014 Society of Plastics Engineers